Dari Lisan ke Tulisan: Penyusunan Modul Tenun untuk Pelestarian Budaya dan Pemberdayaan Masyarakat Bonen: From Oral to Written: Developing a Weaving Module for Cultural Preservation and Community Empowerment in Bonen - Lakapu, Meryani; Leton, Samuel Igo; Mberu, Yuliana Bhara; Sau, Antonius Arnoldus Janssen; Benu, Cindy Ahia Pricilia (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
This community service program was carried out in Bonen Village, Kupang Regency, aiming to preserve traditional weaving culture while empowering women and young generations. The leading partner of this activity was the Ume Halan Foundation, which mentors the Pasuklo Weaving Community. The primary problems identified were the lack of regeneration of young weavers and the absence of written guidelines for the weaving learning process. The program was implemented through a participatory approach comprising several stages: preparation and socialization; focus group discussions to enrich data; module revision and trials; training on module use; and continuous mentoring and evaluation. The outcome of this program is a locally wisdom–based weaving module that introduces motifs, basic weaving techniques, tools and materials, and the use of natural dyes. The module was produced in both printed and digital formats to ensure accessibility across generations. The training involved approximately 15 elementary school students from SD Inpres Bonen and 12 senior weavers from the Pasuklo Community. The participatory evaluation showed that 80% of participants found the module easy to understand and engaging, and that teachers and local weavers agreed it effectively facilitated intergenerational knowledge transfer. Overall, this program contributes to cultural preservation, women's empowerment, and the revitalization of young weavers in Bonen Village, while strengthening Ume Halan's role as a sustainable community learning center.